Fostering ICT-Competences and Critical Thinking Skills Framework as 21st Century Skills in Learning Activities General English (GE) Syllabuses - Khilda Shopia; Muhammad Rizky Fadhil (English Language in Focus (ELIF), 2023)
As the part of 21st century skill, beside ICT competence, critical thinking skill is important to be trainned. This research was conducted to analyze and explore critical thinking skills and ICT competences in the learning activities of GE syllabuses. Principally, critical thinking skills is categorized as Higher Order Thinking Skills (HOTS) that is discussed in Anderson and Krathwohl’s Taxonomy Cognitive levels. A content analysis method was employed in this study. The data was analyzed by using a systemic content descriptive text based on the Framework from ACER’s Critical Thinking Skill Development, UNESCO ICT-competences framework (2018), Anderson and Krathwohl's Taxonomy's cognitive levels and ACTS21S framework descriptors. 8 syllabuses of General English were analyzed from 6 private and 2 public university in Banten and West Java area. The existing syllabuses were collected to investigate how far Critical Thinking skills and ICT-competences foster into the learning activities stated in the syllabuses. The findings illustrated that critical thinking skills throughout full syllabuses were insufficiently incorporated with learning activities. Dominantly, the 1st strands of Knowledge Construction fostered in syllabuses by 76%. Besides, in HOTS level, the analyse level (75%) was dominantly integrated in the learning activities by stating the action verbs such as Menganalisis, Menentukan, Menguraikan, Membedakan. Then, ICT-competences was employed in the learning activities as media and tools to support teaching and learning activities such as to access relevant material through internet device (website), to support learning activities by using hardware and software. The result also illustrated 5 procedures in fostering critical thinking skills and ICT competences in learning activities in syllabuses.